Comparative contamination of Listeria monocytogenes in traditional dairy products in Esfahan Province, Iran (African Journal of Dairy Farming and Milk Production, 2013)
Listeria monocytogenes, a primary human pathogen, has been found in different places in the environment of dairy, and the bacterium may survive for a long time in a dairy. L. monocytogenes is a major concern for the food industry, as it can cause listeriosis in humans. Listeriosis is one of the most important infections in Europe and the United States. It may cause fever, muscle aches and gastroenteritis; but does not usually cause septicaemia in healthy non-pregnant individuals. In pregnant women, it may cause abortion or neonatal death. From June 2010 to April 2012, a total of 420 samples were collected from different places in Esfahan Province. Samples were collected and analyzed based on the International Organization for Standardization using cultural method and biochemical test. Totally, in 57 samples (13.57%) of 420 dairy product samples L. monocytogenes was isolated. Based on biochemical observation, out of 210 raw milk samples, 42 (20%) were contaminated by Listeria monocytogenes. In traditional butter samples, 9 samples were contaminated by L. monocytogenes (12.85%); in traditional cheese samples, 5 (7.14%) samples were contaminated by L. monocytogenes and in traditional curd samples, 1 sample was contaminated by L. monocytogenes (1.43%). According to our finding, using traditional dairy products is dangerous, and it must be controlled by the ministry of health organization or other related organizations.